The World by Religion - Johnson, Todd M. (Journal of religion and demography, 2023)
This article represents the results of analysis of data on religion for all of the countries of the world which appear in the World Religion Database (Johnson and Grim 2023). Data was collected at the national level from a number of sources including censuses, surveys, polls, religious communities, scholars, and others. After data collection and analysis, discrepancies were worked out and best estimates are made for each religion across a number of years. Results are presented for religionists and non-religionists as a whole as well as for each religious and non-religious category.